Investasi Hama Penggerek Pucuk Kelapa (Oryctes rhinoceros) Pada Plasma Nutfah Agave - Parnidi Parnidi; Dwi Adi Sunarto; Marjani Marjani (BIOEDUSCIENCE, 2022)
Background: Agave is known as one of the natural fiber-producing plants that have many benefits. Agave plants can grow well on dry land, however, many organisms can damage agave crops in the field. One of the agave plant is Shoot Borers Beetle Pest of Coconut (Oryctes rhinoceros L). The purpose of this research is to get information about variation damage of agave germ plasma to Shoot Borers Beetle Pest of Coconut (Oryctes rhinoceros L). Methods: The research was conducted at the Agave balittas collection in the Experimental Garden Balittas Karangploso. Observation of shoot borers beetle pest of coconut (Oryctes rhinoceros L.) was carried out on 6 plants. Observations were made by calculating the number of holes that were found on the leaves. Results: The results showed that the investment of Shoot Borers Beetle Pest of Coconut (Oryctes rhinoceros L) causing damage to agave germplasm varies. The average percentage of damage to Agave angustifolia and Agave cantala in 2017 due to the investment in Shoot Borers Beetle Pest of Coconut (Oryctes rhinoceros L) is range from 66.7 to 100%. The average damage caused by Shoot Borers Beetle Pest of Coconut (Oryctes rhinoceros L) investment in Agave sisalana ranges from 0 to 16.7%. Conclusions: The investment of shoot borers beetle pest of coconut in agave plants has a big impact on decreasing crop production and fiber quality.